Implementation of Law Protection of the Equal Rights for People with Disabilities in Aerial Transportation - Putra, Willy (The Center for Disability Studies and Services Brawijaya University, 2019)
Rights in human rights have a position or prime and first degree in community life Article 28I Paragraph 2 of the 1945 Constitution provides that everyone is free from discriminatory treatment. However, discriminatory treatment still occurs misses in the case of Dwi Aryani Vs Etihad Airways which is derived by the airline on the grounds that he is a person with disabilities who are in wheelchairs and no counselors. How the implementation of legal protection by airlines on equal rights for groups of People with disabilities in aviation transport The author examines this issue using legal research methods for academic purposes. The research data shows that the airport does not yet have complete facilities for groups of People with disabilities, the absence of technical regulations / implementers that further regulate the Law No. 8 of 2016, lack of socialization and education to the public, airport service providers, airlines, and field officers. This is why the protection of groups with disabilities is less effective. Governments should issue technical / implementing regulations related to the Disability Law, and conduct socialization and education to the public, airport facility providers, airlines and field workers.Groups Of People With Disabilities, Discrimination, Human Rights.